Selection of foundation type of hospital building using analytical hierarchy process - Hutahaean, Aswin Vincentius; Iskandar, Isdaryanto (Desimal: Jurnal Matematika, 2023)
In order to develop the Ministry of Defense Hospital dr. Suyoto in Bintaro, South Jakarta, a new 27-storey building will be built on the south side of the hospital complex. This study aims to select the type of foundation that is able to support the building above it, but with minimal disturbance due to vibration, noise, mud, and excavation, because the hospital must continue to operate, and relates to aspects of cost, time, and scope. The method used is the Analytical Hierarchy Process (AHP) involving five respondents who are considered construction experts from the Construction Center (Puskon) officers, planning consultants, supervisory consultants, and contractors. The results of the study found that concrete pile foundations with Hydraulic Static Pile Drivers (HSPD) were the most suitable for new building foundations from the five criteria and four alternative choices of foundations. In the detailed design process by the planning consultant, several pile caps were found that coincide with each other so it was decided to combine them into a large pile cap which also functions as a raft foundation. So that in its implementation, a combination of concrete piles with HSPD and raft foundations is used.